Migrant crossings: witnessing human trafficking in the U.S - Fukushima, Annie Isabel (Stanford University Press, 2019)
An American haunting : witnessing human trafficking and ghostly exclusions -- Legal control of migrant crossings : citizenship, labor, and racialized sexualities -- "Perfect victims" and labor migration -- Witnessing legal narratives, court performances & translations of domestic work -- (Living)dead subjects : mamasans, sex slaves, and sexualized economies.